Food Safety: Cook It Safely - Jennifer Hillan (EDIS, 2007)
Revised! FCS8633, a one-page fact sheet by Jennifer Hillan, provides a handy chart that informs consumers what temperatures foods need to reach before they are safe to consume. Published by the UF Department of Family, Youth and Community Sciences, August 2006.